THE MEANING OF LIFE’S DILEMMA IN SELECTED POEMS OF ROBERT FROST: A SEMIOTIC ANALYSIS BASED ON PEIRCE - Nofansyah (Prologue: Journal on Language and Literature, 2026)
This research analyzes the meaning of life’s dilemmas in five selected poems by Robert Frost using Charles Sanders Peirce’s semiotic theory. The poems examined in this study include The Road Not Taken, Stopping by Woods on a Snowy Evening, Fire and Ice, Mending Wall, and Nothing Gold Can Stay. The objective of this research is to identify the signs presented in the poems and interpret their meanings related to the dilemmas of human life. This study employs a qualitative descriptive method with a semiotic approach. The analysis applies Peirce’s triadic model of sign consisting of representa-men, object, and interpretant to interpret the symbolic elements found in the poems. The findings reveal that Robert Frost frequently utilizes natural imagery such as roads, woods, fire, ice, walls, and seasonal changes as sym-bolic signs representing human experiences and existential conflicts. These symbols illustrate various forms of life dilemmas including decision-making, the tension between personal desire and responsibility, emotional conflict, social boundaries, and the inevitability of change. This study concludes that the application of Peirce’s semiotic framework helps reveal deeper mean-ings embedded in Frost’s poetry and provides a systematic interpretation of how symbolic signs represent the complexities of human life.